Achieving the 2020 vision in the shadow of international terrorism: 2000 World Food Prize Laureate address (October 19, 2001) - Pinstrup-Andersen, Per (2001)
Fighting terrorism involves more than identifying and eradicating its organizers and perpetrators through military and financial means. We must also wage a campaign to eliminate the conditions that propel terrorism: Poverty, hunger, malnutrition, and mismanagement of natural resources.